Public-private partnerships in TVET : adapting the dual system in the United States - Remington, Thomas F. [Verfasser] (My University, 2018)
"Around the world, governments, educators and employers have expressed growing interest in German-style methods of technical and vocational education and training (TVET). In such countries, schools and firms share responsibility for providing technical and vocational education, a model often called the 'dual system of vocational training and education'. The dual system means that occupational training occurs at two linked sites, educational institutions and workplaces. Dual education aims at matching the demands of a dynamically changing economy with the skill profiles of those graduating from educational institutions. To a large extent, dual education systems enable young people to acquire not simply technical and occupational skill, but broadly defined competencies that serve as the foundation for rewarding careers and social esteem. Little wonder that many countries have turned with renewed interest to the dual TVET system. However, actual implementation of the dual system outside the core Germanic countries in Europe has proven to be extremely challenging. Successful examples of institutional transplantation are rare. However, in some countries, local partnerships embracing elements of dual education have formed, uniting educational institutions, government entities and firms in partnerships to upgrade TVET. This paper discusses some of the characteristic patterns of such partnerships in the U.S." (Author's abstract, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 2.3 Berufsbildungspolitik; I 1 Internationale Berufsbildung; I 2.1 Deutschland; I 2.3.2 Nordamerika; Betriebliche Berufsausbildung; Duales System; Berufsbildungspolitik; Bildungstransfer; Public-private-Partnership; Internationale Zusammenarbeit; Bundesrepublik Deutschland; USA